The Effect of Expressive Writing Techniques on Reducing Academic Anxiety in Medical Profession Students in Makassar - Azzahra, Nurul Izzah; Ridfah, Ahmad; Nurdin, Muh. Nur Hidayat (ARRUS Journal of Social Sciences and Humanities, 2023)
Medical profession students have a high level of academic anxiety, one of the interventions that can reduce expressive writing. This study aims to determine the effect of expressive writing techniques on reducing academic anxiety in medical profession students in Makassar. This study used a Pretest Post-test Control Group Design. The research participants were medical profession students from several universities in Makassar, totaling 6 experimental groups and 6 control groups. The measuring instrument used in this study was the academic anxiety scale. Data analysis techniques using Wilcoxon and Mann Whitneyy hypothesis tests. The results showed that expressive writing can reduce academic anxiety scores in medical profession students. The results of the Mann Whitney test, namely p = 0.004, show that there are differences in academic anxiety scores in the experimental and control groups. Wilcoxon test results are p=0.028 for the experimental group and p=0.783 for the control group. The results of this study found that the posttest score owned by the experimental group (mean = 90) was lower than the control group (mean = 113). The implication of this study is that expressive writing can be used as one of the media to reduce academic anxiety of medical profession students.